The Condition of Life of Immigrants from Africa and Latin-America in Barcelona - (:unkn) unknown (My University, 1996)
The phenomenon of immigration in Catalonia and in the Metropolitan Area of Barcelona is not new. Infact, in the last century, the immigration has been the key of the demographic system of both areas. The immigrant population from Spain, that was massive in the 60s, has diminished since 1975. Since that date, coinciding with the economical crisis, we can notice the increase of foreign immigrant population. Immigration from Africa and Latin-America is one of the immigration that has suffered a bigger increase. This paper exposes some reflections about the indicators of the integration of migrants. They stem from the analysis of the conditions of life of foreign immigrant population from Africa and Latin-Ammerica, realized in 1994 by the Metropolitan Studies Institute of Barcelona.
Keywords: African Research